2011
DOI: 10.1007/s10709-011-9604-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of evolutionary dynamics of genes encoding leucine-rich repeat receptor-like kinase between rice and Arabidopsis

Abstract: The leucine-rich repeat (LRR) receptor kinase (RLK) proteins constitute a large superfamily in the plant genome, and carry out key functions in a variety of biological pathways. In an effort to determine the evolutionary fate of members of a large gene family such as plant LRR RLK proteins we conducted in silico analysis using complete genome sequencing datasets, genome-wide transcriptome databases, and bioinformatics tools. A total of 292 and 165 LRR RLK genes were retrieved from the rice and Arabidopsis geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…PtLRR-RLK genes were comprehensively distributed within the poplar genome and 22 genes are localized to unassembled genomic sequence scaffolds and thus could not be mapped to any particular chromosome (Figure 3). Approximately 82% (312 out of 379) PtLRR-RLK genes are located in the replicated region, which is different from rice and Arabidopsis in which the frequencies of genes generated by S/WGDs are much lower (11% in rice and 26% in Arabidopsis ) [45]. Among them, 140 genes lacked duplicates on the corresponding duplicated blocks, suggesting that dynamic rearrangement, mutation or segmental loss may have occurred following the segmental duplication.…”
Section: Resultsmentioning
confidence: 99%
“…PtLRR-RLK genes were comprehensively distributed within the poplar genome and 22 genes are localized to unassembled genomic sequence scaffolds and thus could not be mapped to any particular chromosome (Figure 3). Approximately 82% (312 out of 379) PtLRR-RLK genes are located in the replicated region, which is different from rice and Arabidopsis in which the frequencies of genes generated by S/WGDs are much lower (11% in rice and 26% in Arabidopsis ) [45]. Among them, 140 genes lacked duplicates on the corresponding duplicated blocks, suggesting that dynamic rearrangement, mutation or segmental loss may have occurred following the segmental duplication.…”
Section: Resultsmentioning
confidence: 99%
“…If the paralogous extensins had expanded neither through W/SGD nor TD, they were considered to have proliferated via other duplication strategies [33]. …”
Section: Methodsmentioning
confidence: 99%
“…Whole-genome studies have further shown that genes encoding the largest RLK subfamily of LRR RLKs covary significantly between species in terms of numbers and structure and therefore have been predicted to possess similar functions (Hwang et al, 2011;. Their evolutionary conservation therefore circumvents the problematic genetic differences between model and crop species and allows global extrapolation after LRR RLK studies have been performed in model plants (Shiu et al, 2004).…”
Section: A New Approach: Rlks and Drought Stressmentioning
confidence: 99%